Bimbingan Teknis Menyusui terhadap Pengetahuan, Keterampilan dan Efikasi Diri Ibu Menyusui - Yuli Suryanti; Ajeng Galuh W; Pauline Kusmaryati (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of breastfeeding technical guidance on the knowledge, skills, and self-efficacy of breastfeeding mothers. This research is pre-experimental research with the approach used as One Group Pretest-posttest. The results showed that breastfeeding technique guidance was very influential in increasing breastfeeding knowledge, skills, and self-efficacy with a value of = 0.000 (p <0.05). In conclusion, providing education about breastfeeding techniques is effective in increasing knowledge, skills, and self-efficacy in breastfeeding. Keywords: Breastfeeding, Guidance, Self-Efficacy, Counseling